App-Based Delivery of Clinical Emotional Freedom Techniques: Cross-Sectional Study of App User Self-Ratings - Church, Dawson; Stapleton, Peta; Sabot, Debbie (JMIR Publications, 2020)
BackgroundThe burgeoning area of mobile health (mHealth) has experienced rapid growth in mobile apps designed to address mental health issues. Although abundant apps offer strategies for managing symptoms of anxiety and stress, information regarding their efficacy is scarce. ObjectiveThis study aimed to assess the effect of an mHealth app on user self-ratings of psychological distress in a sample of 270,461 app users. The Tapping Solution App guides users through the therapeutic protocols of Clinical Emotional Freedom Techniques (EFT), an evidence-based psychophysiological intervention that combines acupressure with elements of cognitive and exposure therapies. MethodsApp users provided self-ratings of emotional intensity before and after app sessions (termed "tapping meditations") using an 11-point Subjective Units of Distress scale. App user data for 23 tapping meditations, which addressed psychological symptoms of anxiety and stress, were gathered between October 2018 and October 2019, totaling 380,034 completed app sessions. ResultsAcross 12 anxiety-tapping meditations, the difference in emotional intensity ratings from presession (mean 6.66, SD 0.25) to postsession (mean 3.75, SD 0.30) was statistically significant (P<.001; 95% CI −2.92 to −2.91). Across 11 stress-tapping meditations, a statistically significant difference was also found from presession (mean 6.91, SD 0.48) to postsession (mean 3.83, SD 0.54; P<.001; 95% CI −3.08 to −3.07). The results are consistent with the literature on the efficacy of Clinical EFT for anxiety and stress when offered in conventional therapeutic formats. ConclusionsThe findings provide preliminary support for the effectiveness of the mHealth app in the immediate reduction of self-rated psychological distress. As an adjunct to professional mental health care, the app promises accessible and convenient therapeutic benefits.